The Impact Of Non-Financial Incentives On Intention To Stay: A Study Among Malaysian Nurses In Private Hospitals - Krishnamoorthy, Lalitha (2014)
Extended longevity and increase in hypertension, cardiovascular ailments and diabetes has made Malaysia's healthcare industry a powerful area of economic growth towards nation's income. Maintaining adequate and stable nursing workforce is vital to meet the industry's escalating demand amidst global and local shortage of nurses especially for skilled and experienced nurses. The present study aims to determine the impact of non-financial incentives (NFls) and to identify which of the eight dimensions of non-financial incentives has significant influence on intention to stay among Malaysian nurses in private hospitals. A cross sectional questionnaire survey was administered on 630 nurses in 52 Klang Valley private hospitals, response rate was 26%, (n=161). The collected data includes items measuring eight dimensions of nonfinancial incentives as independent variable (education, training and professional development, recognition, promotional opportunities, flexible working arrangements, autonomy and control over nursing practice, manageable workload, management and supervisory support and work environment) and intention to stay as the dependent variable. The findings explained 54% of variance in nurses' intention to stay.